Gender Differences in Individuals at High-Risk of Psychosis: A Comprehensive Literature Review. (1st January 2015) - Barajas, Ana; Ochoa, Susana; Obiols, Jordi E.; Lalucat-Jo, Lluís
Abstract : Introduction . To date, few studies have focused on the characterization of clinical phenomenology regarding gender in population at high-risk of psychosis. This paper is an attempt to summarize the findings found in the scientific literature regarding gender differences in high-risk populations, taking into account parameters studied in populations with schizophrenia and other psychotic disorders, such as incidence, clinical expression, duration of untreated illness (DUI), social functioning, and cognitive impairment prior to full-blown psychosis development. Method . Studies were systematically searched in PubMed. Studies using gender variable as a control variable were excluded. 12 studies met inclusion criteria. Results . Most of the studies found a differential pattern between women and men as regards clinical, social, and cognitive variables in the prodromal phase, with worse performance in men except in cognitive functioning (more severe negative symptoms, worse social functioning, and longer DUI in men). Similar conversion rates over time were found between men and women. Conclusions . Many of the studies analyzed suggest that differences between men and women in the expression of psychosis extend across a continuum, from the subclinical forms of illness to the debut of psychosis. However, the small number of studies and their significant methodological and clinical limitations do not allow for firm conclusions.